2004
DOI: 10.5301/jbm.2008.5643
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of albumin in bronchial washing fluid of patients with bronchial carcinoma. Could albumin be considered as a tumor marker?

Abstract: Measurement of albumin levels in BWF could be a useful additional diagnostic tool to differentiate malignant from non-malignant lung diseases. Moreover, the combined measurement of CEA in serum and albumin in BWF could be of aid in the follow-up of lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Therefore, we propose that the interstitial entry of large plasma proteins, such as factor H, reflects an increase in microvascular permeability of the tumor circulation. In agreement with these results, Charokopos et al (20) showed that bronchial washings from patients with lung carcinoma present an increased concentration of albumin. The authors found that the determination of albumin in bronchial washings had a high sensitivity and specificity for the diagnosis of lung cancer and suggested that the presence of albumin in the bronchial fluid was caused by its exudation to the bronchial lumen.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, we propose that the interstitial entry of large plasma proteins, such as factor H, reflects an increase in microvascular permeability of the tumor circulation. In agreement with these results, Charokopos et al (20) showed that bronchial washings from patients with lung carcinoma present an increased concentration of albumin. The authors found that the determination of albumin in bronchial washings had a high sensitivity and specificity for the diagnosis of lung cancer and suggested that the presence of albumin in the bronchial fluid was caused by its exudation to the bronchial lumen.…”
Section: Discussionsupporting
confidence: 75%